Arrhythmia recognition from electrocardiogram using non-linear analysis and unsupervised clustering techniques - Sun, Yan. (2008)
In this dissertation, a new analytical framework for arrhythmia recognition in ECG signals using nonlinear analysis and unsupervised clustering techniques is developed. The problem of ECG signal conditioning, ECG episode characterization, characteristic wave detection, and arrhythmia recognition, have been tackled in this thesis.